2008
DOI: 10.1007/s00423-008-0380-9
|View full text |Cite
|
Sign up to set email alerts
|

The use of “harmonic scalpel” versus “knot tying” for conventional “open” thyroidectomy: results of a prospective randomized study

Abstract: HS is a safe alternative to KT, allowing for a significant reduction of operative time without increasing complications rate and overall costs and probably better utilization of health resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
91
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(104 citation statements)
references
References 21 publications
10
91
1
2
Order By: Relevance
“…In some studies11, 20, 21, 25, 31, transient hypocalcaemia was less common when US were used but, more often, rates were similar to those in the control arm7, 8, 9, 18, 22, 23, 27, 29, 30. Postoperative pain has rarely been evaluated, and only in a few studies12, 21, 27 did US reduce pain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In some studies11, 20, 21, 25, 31, transient hypocalcaemia was less common when US were used but, more often, rates were similar to those in the control arm7, 8, 9, 18, 22, 23, 27, 29, 30. Postoperative pain has rarely been evaluated, and only in a few studies12, 21, 27 did US reduce pain.…”
Section: Discussionmentioning
confidence: 99%
“…Some found the US device to be cost‐effective in terms of surgical procedure and/or hospital admission24, 28, whereas others8, 9 reported that, owing to the higher cost of disposable materials, the overall cost of hospitalization was not significantly different between US and CH groups. Economic analyses are difficult to extrapolate to different countries because of differences in hospital costs and organization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These devices rely heavily on high-energy sources, including radio waves and ultrasound, with specialized instruments now available specifically for thyroid surgery. [2][3][4][5] Recent studies have suggested that the Harmonic Focus method is associated with higher complication rates, whereas the LigaSure Precise method prolongs the operating time. 6 New scissors have also been introduced to increase efficacy and intraoperative safety.…”
mentioning
confidence: 99%
“…The Harmonic Scalpel FOCUS has an active blade that oscillates at 55 kHz, simultaneously sealing and cutting tissue. This vibration denatures hydrogen bonds, leading to formation of a protein coagulum [5,6]. Thermal spread from either instrument is reported to be 0.5-2 mm and is related to vessel size and hence he corresponding energy required for proper vessel sealing.…”
Section: Introductionmentioning
confidence: 99%